(untitled) (Per Musi, 2018)
This article presents an investigation about the logic of musical expression in the Classicism. Its main reference is the musical theory of Heinrich Christoph Koch (1749-1816), historically considered as the most comprehensive of his time. Starting from the notion of music as a language, Koch conceives units of musical thought that constitute musical speeches, oriented by a specific logic. This logic is performed on the basis of the material, structural and perceptible attributes of the units of thought, enabling the rationalization of its processes and the constitution of a specific musical Grammar and Rhetoric, which regulate the possibilities of usage of the music language. The historical recovery of this logic contributes to the reclaiming of meanings, techniques and values hidden by the historical distance, both of the theory which it constitutes and the repertoire to which it allows to accede. In these terms, it configures itself as a valuable tool of access to the music of its time.